PENGARUH KARAKTERISTIK CORPORATE GOVERNANCE TERHADAP KETERJADIAN RESTATEMENT LAPORAN KEUANGAN - Arum Sekar Kaloka, 12.05.52.0237; Susilowati, Yeye (Students Journal of Accounting and Banking, 2016)
This study aimed the effect of corporate governance characteristics on the financial restatement. Indicators used to measure corporate governance mechanisms in this study is proportion of independent board, proportion of independent audit committee, size of audit committee, institutional ownership,and managerial ownership. This study uses secondary data with entire population companies listed in the Indonesia Stock Exchange (BEI) in 2010-2015. The method used to determine the sample using purposive sampling. Sample contains from 22 restate companies and 22 non-restate companies. The analytical method used is logistic regression. The results of hypothesis testing showed that the proportion of independent board, proportion of independent audit committee, size of audit committee and managerial ownership did not significantly affect on restatement. While the instititional ownership has a sgnificantly negative affect on restatement. Â Keywords:Â Restatement, Corporate Governance, Proportion of Independent Board, Proportion of Independent Audit Committee